الجريمة الانتخابية - دراسة تأصيلية مقارنة – - مفتاح, عبد الجليل; شبرة, أ/ عزيزة (Sciences humaines; Vol. 37 (2014): SCIENCES HUMAINES(Novembre), 2014)
تتناول هذه الدراسة موضوع الجريمة الانتخابية من الناحيتين النظرية والتأصيلية، أي بالتعرض إلى مختلف التعاريف التي سيقت بشأنها وتطورها على المستويين التاريخي والدولي بالنظر إلى الخصوصية التي تميز هذه الجريمة عن غيرها من الجرائم الأخرى في نطاق التشريع العقابي، وهي الخصوصية التي تدفع إلى كشف النقاب عن الطبيعة القانونية لها وذلك فيما إذا كانت الجريمة الانتخابية نوع من الجرائم السياسية أم أنها جريمة عادية، فضلا على ما سبق فان موضوع الجريمة الانتخابية يرتبط بالبحث في أنواعها وصورها المختلفة. This study deals with the crime of electoral both theoretical and Altaeselah ,any exposure to the various definitions that were given them and their development , both historical and international view of the privacy that characterize this crime from other other crimes in the scope of the legislation punitive , a privacy that pay to unveil nature their legal and that whether the crime of electoral kind of political crimes or is it a common crime , as well as on the above, the object of the crime of electoral associated research in their various types.